T-cell polarization: Potential serological markers in preterm and term infants. (October 2016) - Frezza, Simonetta; Gallini, Francesca; Palazzo, Raffaella; Carollo, Maria; De Carolis, Maria Pia; D'Andrea, Vito; Catenazzi, Piero; Romagnoli, Costantino; Ausiello, Clara Maria
Abstract: Background: The immaturity of immune system characterizes newborn infants. Possible serological markers of Th1 and Th2 immune response are the lymphocyte activation gene-3 (CD223) and soluble CD30, respectively (sCD30). Aims: The aim of our study was to evaluate the relationship between Th1 and Th2 immune response and gestational age (GA), comparing data in preterm and term neonates. Study design: Cord blood from 20 preterm (GA: 33 ± 2 weeks, BW 1950 ± 490 g) and 20 term infants (GA: 38 ± 1 weeks, BW: 3177 ± 330 g) were tested for sCD30 and CD223 levels by ELISA. IFNγ levels produced by cord blood lymphocytes were also analyzed, both before and after stimulation with phytohaemagglutinin (PHA). Results: sCD30 resulted significantly higher in preterm neonates when compared with term neonates (60 ± 7.6 vs 42.6 ± 3.9 U/ml p < 0.05). CD223 was undetectable in preterm neonates while resulting at a level of 176.1 ± 112.6 ng/ml in term neonates. After stimulation with PHA, a significant increase in IFNγ levels was only observed in term neonates (326.6 ± 72.7 pg/ml p < 0.05). Conclusions: Our findings show that sCD30 is present and measurable in term and preterm infants, while CD223 is detectable only in term infants and that Th-cell polarization could also depend on gestational age. Our data suggest that a Th2 immune response seems predominant in preterm neonates. Highlights: This study highlights the role of sCD30 and CD223 in preterm and term infants as a possible index of T-Cell polarization. Moreover our results suggest that gestational age plays an important role in determining the Th-driven immune response. The Th-cell response pattern could also be involved in the immune response to vaccines.